PROFIL KONDISI FISIK DAN KETERAMPILAN TEKNIK DASAR ATLET TENIS MEJA USIA DINI DI KOTA SEMARANG - Agus Pujianto (Universitas Negeri Semarang, 2015)
The purpose of this research was to assess the physical condition and basic engineering skills at an early age table tennis athletes in Semarang. The population was table tennis athletes in the city of Semarang, amounting to 36 people. Sampling using total sampling, ie all populations table tennis athletes in Semarang numbered 36 people. Variables include the study of physical conditions and basic technical skills of table tennis . To obtain data, so in this research using survey methods and testing techniques. For the instrument used is the physical condition of the test: sprint (sprint) 30 meter, 1,600-meter run, running back and forth 4x5 meters, sit and reach, sitting on the wall, vertical jump, and flexed Arm Hang. As for the basic skills of table tennis, the test used is the test: grip technique, footwork technique, stroke, block, and service. Data were analyzed using descriptive percentages. The results showed that the physical conditions of table tennis athletes in Semarang included in the medium category. As many as 64% of men and 86% of athletes women athletes in the medium category. Skills table tennis techniques in both categories. A total of 73% men and 93% of athletes women athletes have good basic engineering skills. It was concluded that the profile was moderate physical condition and basic engineering skills in table tennis athletes in Semarang in 2013 in both categories